Criteria of life quality estimation at patients with cerebrovascular pathology - O. A. Tsimeyko; V. V. Moroz; M. R. Kostyuk (Ukrainian Neurosurgical Journal, 2007)
The modern scales for life quality estimation at patients with cerebrovascular pathology are presented. Standardization of scales application is executed at different types of vascular pathology. Application of the system for stroke severity estimation helps to make objective decision for treatment tactics and strategy. The complex use of scales with balls give a possibility to improve prognosis for period after stroke course, to estimate conservative therapy and surgical treatment efficiency at patients with acute violation of cerebral blood circulation.